Beyond Collection and Disposal: Assessing the Potential of 3Rs Implementation for Municipal Solid Waste Reduction in Bangladesh - Shumshunnahar, Mst (Open Access Indonesia Journal of Social Sciences, 2024)
The rapid urbanization and population growth in Bangladesh have resulted in a substantial increase in municipal solid waste (MSW) generation, posing a significant challenge to traditional waste management practices that primarily focus on collection and disposal. This study explores the potential of implementing the 3Rs (Reduce, Reuse, Recycle) to address this escalating waste crisis and transition towards a more sustainable waste management approach. A mixed-methods approach was employed, encompassing a comprehensive literature review and primary data collection through surveys and interviews. The literature review examined existing waste management practices in Bangladesh and the potential benefits of 3Rs implementation. Surveys and interviews were conducted with key stakeholders, including municipal authorities, waste management professionals, and residents, to gain insights into current waste management challenges and perceptions regarding 3Rs adoption. The findings revealed that current waste management practices in Bangladesh are predominantly reliant on collection and disposal, with limited emphasis on 3Rs. The lack of awareness, infrastructure, and economic incentives were identified as major barriers to 3Rs implementation. It is estimated that through effective 3Rs implementation, MSW disposal in Bangladesh can be reduced by 60-85%. This study underscores the urgent need to move beyond collection and disposal and embrace 3Rs as a cornerstone of sustainable waste management in Bangladesh. Recommendations include raising public awareness, developing infrastructure, and providing economic incentives to promote 3Rs adoption. By implementing these measures, Bangladesh can effectively address its waste crisis and transition towards a circular economy, fostering environmental protection, resource conservation, public health improvement, and economic development.